Pengaruh Gaya Kepemimpinan, Motivasi Kerja, dan Budaya Organisasi Terhadap Disiplin Kerja Pegawai Kecamatan Tasikmadu Kabupaten Karanganyar - Putriana Wahyuningsih; Sutarno (PENG: Jurnal Ekonomi dan Manajemen, 2025)
This research aims to analyze the significant influence of leadership style, work motivation and organizational culture on the work discipline of employees in Tasikmadu District, Karanganyar Regency. The type of data used in this research is quantitative data. The data source used is primary data. The sample in this study was 39 employees of Tasikmadu District, Karanganyar Regency. The method used for sampling was a saturated sampling technique. Data collection techniques in this research used observation, questionnaires and literature study. Test the research instrument using validity and reliability tests. The classical assumption test uses tests: multicollinearity, autocorrelation, heteroscedasticity and normality. Data analysis techniques use multiple linear regression tests, t tests, F tests and R2. The results of the validity and reliability tests show that all statements regarding the variables of leadership style, work motivation, organizational culture and work discipline are declared valid because the p-value is <0.05 and reliability is because the Cronbach's alpha value is >0.60. The results of the classical assumption test show that all variables have passed the tests for multicollinearity, autocorrelation, heteroscedasticity and the residuals are normally distributed. The results of the regression analysis obtained the equation Y = - 1.636 +0.382 X1 + 0.242 X2 +0.459 X3. The results of the t test show that leadership style (X1), work motivation (X2), organizational culture (X3) have a significant effect on the work discipline of employees in Tasikmadu District, Karanganyar Regency. The results of the F test showed that the regression model used in this research was correct. The R2 results show that the contribution of the independent variable to the dependent variable is 92%, the remaining 8% is influenced by other factors outside the variables studied.